Behaviour of continuous deep beams with unsymmetrical web openings - Tham, Win Yen (Nanyang Technological University, 2021)
It is important to understand that deep beams behave differently from normal beams. Due to their dimensions, deep beams are predominantly controlled by shear strength. Precise analytical study on reinforced concrete deep beams has always been a complex issue and the presence of web openings in continuous deep beams exacerbates the situation. Thus far, no code provisions are available for the evaluation of such beams. Besides, there are very few investigations performed on continuous deep beams with web openings.